Adaptive Leadership: Regional Leaders Respond to the Pressure of 8 Percent Economic Growth in Indonesia - Jotha Scorda; Ayu Rahmawati Oktavia; Johannes Johannes (Sean Institute, 2025)
This study analyzes the need for adaptive leadership in responding to various central government pressures on regional governments fiscal pressures and demands for regional economic growth, particularly in the context of the eight percent national growth target. Through a Systematic Literature Review (SLR) approach to 30 articles published between 2020 and 2025, this study integrates three main concepts: fiscal stress, regional economic structure, and adaptive leadership. The analysis shows that fiscal stress significantly influences development capacity, especially in regions dependent on commodities. Adaptive leadership is proven to be a key variable that enables regional governments to maintain development stability through innovative strategies, cross-sector collaboration, and economic diversification. This study offers an integrative conceptual model that emphasizes the importance of adaptive capacity as a foundation for resilient regional governance.